Bhendi Growth and Biochemical Characteristics in Response to Foliar Application of Plant Growth Regulators - Baliah, Neeldurai Tensingh; Muthulakshmi, Pitchaikani; D, Dharmaraj (Asian Journal of Biological and Life Sciences, 2016)
The present study was aimed to find the stimulatory effect of certain plant growth regulators such as IAA, BAP, GA, Spic Cytozyme, and Aminos on the growth and biochemical characteristics of bhendi (Abelmoschus esculentus (L.) Moench). The results revealed that the plants growth regulators had a positive impact on bhendi plant growth as well as in the some biochemical aspects when they were sprayed as foliar. Further, the stimulatory effect with reference to shoot and root development was higher in plants sprayed with Spic Cytozyme. In the case of biochemical parameters, the stimulatory effect was varied among the plant growth regulators. There was a significant increase in all biochemical parameters except NR activity. There was not much variation in the NR activity with all plant growth regulators but better than the control plants.
Keywords: Bhendi; Biochemical; Growth; Plant growth regulators